A study on the fatigue performance of a glass fiber-epoxy polymer nanocomposite under random loads. Issue 3 (August 2015) - Jagannathan, N.; Anilchandra, A. R.; Manjunatha, C. M.
<x content-type="archive" xml:space="preserve">Abstract</x> A glass-fiber reinforced plastic (GFRP) nanocomposite containing 10 wt-% silica nano particles in the epoxy matrix was fatigue tested under a standard helicopter random load sequence, Helix-32. Fatigue life was determined at various reference stresses. The stiffness variation and the matrix crack density in the test specimen were monitored at regular intervals during the fatigue test. The random load fatigue life of the GFRP nanocomposite was about four times higher than that of its neat counterpart over the entire range of reference stress levels investigated. The suppressed matrix cracking and reduced crack/delamination growth rate in nanocomposite were responsible for fatigue life enhancement. Further, the random load fatigue life was predicted by empirical method using constant fatigue life diagrams. Three different damage accumulation models, namely, Palmgren–Miner (PM), Broutman–Sahu (BS) and Hashin–Rotem (HR), were used. All the three models predicted similar results, and a good correlation was observed between experimental and predicted fatigue life.